Enhancing the Digital Competence of Maritime Education Faculty in the Philippines Using DigComp 2.0 Framework - Cabaron, Richard R. (Future Science / FSH-PH Publications, 2023)
Digital Competence is seen as a driver for educational innovation since its immediate result is the production of new digital media resources for teaching. This study aimed to determine the digital competence of maritime education faculty in the Philippines, particularly in the Zamboanga Peninsula. The descriptive method used a survey questionnaire for Seventy-three (73) Maritime Education Faculty. Results revealed that Maritime education faculty are very competent, particularly in information and data, literacy, communication and collaboration, and digital content creation. In the dimensions of safety and on the problem -solving skills, the faculty perceived themselves as Competent. The researcher concluded that some aspects of the digital competence of the faculty need to be enhanced to enable them to successfully handle and deal with digital technologies. Thus, it is recommended that there is a need to enhance their problem-solving skills in online environments to enable them to be careful and produce creative and innovative when confronted with technical problems in their handling of digital technologies.